LACTASE DEFICIENCY IN BABIES AND INFANTS - E.A. Kornienko; N.I. Mitrofanova; L.V. Larchenkova ("Paediatrician" Publishers LLC, 2006)
Lactose, the constituent disaccharide of milk and other dairy products, is an important nutrient in early childhood. Lactase breaks down lactose in small intestine. In most people the activity of lactase reduces with age. In infancy lactase deficiency tends to be either transient, which is more often, or secondary to intestinal diseases. Abdominal cramps, anxiety and dyspepsia are the common symptoms of lactase deficiency. Tactics of treatment should take into account a cause and severity of the condition. A specialized milk formula «enfamil lactofree», distinguished for its' optimal formulation, high clinical effectiveness and good tolerance, could be recommended for use in children with primary, transient and secondary lactase deficiency who receive formula and mixed feeding. Key words: lactose, lactase deficiency, lactose-free formula.